Iron deficiency as energetic insult to skeletal muscle in chronic diseases. Issue 5 (4th September 2018) - Dziegala, Magdalena; Josiak, Krystian; Kasztura, Monika; Kobak, Kamil; von Haehling, Stephan; Banasiak, Waldemar; Anker, Stefan D.; Ponikowski, Piotr; Jankowska, Ewa
Abstract: Specific skeletal myopathy constitutes a common feature of heart failure, chronic obstructive pulmonary disease, and type 2 diabetes mellitus, where it can be characterized by the loss of skeletal muscle oxidative capacity. There is evidence from in vitro and animal studies that iron deficiency affects skeletal muscle functioning mainly in the context of its energetics by limiting oxidative metabolism in favour of glycolysis and by alterations in both carbohydrate and fat catabolic processing. In this review, we depict the possible molecular pathomechanisms of skeletal muscle energetic impairment and postulate iron deficiency as an important factor causally linked to loss of muscle oxidative capacity that contributes to skeletal myopathy seen in patients with heart failure, chronic obstructive pulmonary disease, and type 2 diabetes mellitus.